PENGETAHUAN IBU HAMIL TENTANG ASUHAN KOMPLEMENTER KEHAMILAN BERDASARKAN KARAKTERISTIK DI TPMB PONIRAH MARGOREJO METRO SELATAN KOTA METRO - Martini; Yoga Triwijayanti; Prasetyowati; Ranny Septiyani (Melati Institute, 2023)
Maternal mortality rate (MMR) is one of the indicators to see the success of maternal health efforts. MMR is the ratio of maternal deaths during pregnancy, childbirth, and puerperium caused by pregnancy, childbirth, and puerperium or their management but not due to other causes such as accidents or incidental in every 100,000 live births. MMR in Indonesia is 4,221 deaths, the most common causes of maternal deaths are bleeding (1,280 cases), infection in pregnancy (1,066 cases) and infection (207 cases) (Indonesian Ministry of Health, 2020: 27).Complementary care in some midwifery communities has become an important part of midwifery practice. One of the reasons complementary midwifery care is now widely used is the desire to avoid the side effects of drugs. Complementary midwifery care that can be implemented to pregnant women includes: yoga, aromatherapy, massage. The purpose of this study was to determine the knowledge of pregnant women about complementary in pregnancy based on maternal characteristics at TPMB Ponirah. The population of this sample was pregnant women with a gestational age of 8 weeks to 40 weeks who were healthy with a total of 71 people. The research sample was 61 pregnant women.This study is a quantitative study, with a cross sectional method. Univariate and bivariate data analysis with chi square. The research object was pregnant women TM 1 to 3, the research subject was the knowledge of pregnant women with complementary therapies. The measuring instrument uses a questionnaire, how to measure the questionnaire.The results of the study obtained most of the respondents who had good knowledge about complementary pregnancy were 33 respondents (54.1%). There is a relationship between exposure to information media, parity, employment with complementary pregnancy knowledge. There is no relationship between maternal age and education with complementary pregnancy knowledge.Suggestions for the need for socialization of complementary techniques at Puskesmas, mother's classes and TPMB to overcome complaints during pregnancy so as to minimize the use of drugs that harm the mother and fetus.